Aliran Feminis dan Teori Kesetaraan Gender dalam Hukum - Nur Azizah (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
Feminists are a driving group with different thinking patterns in the concept of gender equality. In the late 1960s until the 70s, feminist groups began to focus their attention on the legal field so that a feminist genre called Feminist Legal Theory emerged. However, this feminist school is influenced by previous thinking. Law is the focus of attention because the law is a legal tool to ratify and strengthen the patriarchal system. Law in a country is seen as unable to accommodate women's rights and only strengthens the position of men. This research is descriptive-analytical research with a literature study. Abstrak Feminis adalah kelompok penggerak dengan pola pemikiran yang berbeda dalam konsep kesetaraan gender. Pada akhir tahun 1960 hingga tahun 70-an kelompok aliran feminis mulai memfokuskan perhatiannya di bidang hukum sehingga muncullah aliran feminis yang disebut Feminist Legal Theory. Meskipun demikian aliran feminis ini dipengaruhi oleh pemikiran sebelumnya. Hukum menjadi focus perhatian disebabkan hukum adalah alat yang legal untuk mengesahkan dan menguatkan system patriarki. Hukum dalam suatu negara dipandang tidak mampu mengakomodir hak-hak perempuan dan hanya menguatkan kedudukan laki-laki. Penelitian ini adalah jenis penelitian deskriptik analitik dengan studi pustaka.